A trilha como o lugar da coisa toda: as trilhas da Ilha Grande como lugares turísticos - Pereira Ostanello, Mariana Cristina; Manhães Prado, Rosane (RITUR - Revista Iberoamericana de Turismo, 2021)
The trail, the place where all things happen: the trails of Ilha Grande as tourist places Abstract: llha Grande, located on the southern coast of the state of Rio de Janeiro, stands out for trekking tourism as it has a wide circuit of well-structured and signposted trails. The trails of Ilha Grande are historical paths which were established over the centuries, ever since pre-colonial indigenous peoples lived there, and have had different uses and configurations until today, when tourism is predominant. This paper presents, from an ethnographic perspective, facts as well as public and private actions that contributed to the island's trails being re-signified over time and transformed into places and tourist resources. Tim Ingold's anthropological theory, which proposes that life is built along paths and tracks, was an inspiration for this research based on direct observation, face-to-face and online interviews, and bibliographic research. We show how the trails of Ilha Grande were constituted and have been used over time by different people in different circumstances, and we also show that the meanings of the trails for trekkers and for local residents follow opposite logics: for the trekkers the trail is a place of pleasure or leisure, and for the island’s residents, the trail is the place of work and life flowing.